Under cadmium stress, silicon has a defensive effect on the morphology, physiology, and anatomy of pea (Pisum sativum L.) plants - El-Okkiah, Samira A. F.; El-Tahan, Amira M.; Ibrahim, Omar M.; Taha, Mohamed A.; Korany, Shereen Magdy; Alsherif, Emad A.; AbdElgawad, Hamada; Abo Sen, Esmaeel Z. F.; Sharaf-Eldin, Mohamed A. (Frontiers in Plant Science, 2022)
Soil pollution with cadmium (Cd) is a serious threat to plant growth and development. On the other hand, silicon (Si) can support plants to cope with Cd stress. However, the Cd stress mitigating impact of Si reduction in pea (Pisum sativum L.) is not known. The objective of this study is to see if and how Si can reduce Cd toxicity. To the end, a greenhouse pot experiment was performed twice during the 2018/2019 and 2019/2020 seasons to investigate the effect of Si on the growth, anatomy, and biochemistry of Cd stressed peas plants. Cd exposure increased the contents of Cd ions in the root and shoot of pea plants. Consequentially, Cd accumulation in pea tissue significantly reduced plant growth i.e., plant height, leaf area, and shoot and root dry weights. The effect of Cd was concentration-dependent, where at low concentration (50 mg/kg soil), the plant height was 94.33 and 97.33cm and at high concentration (100 mg/kg soil), it was 89.0 and 91 cm in the two seasons, respectively. This growth reduction can be explained by the decrease in plants' photosynthesis, whereas plants exposed to Cd toxicity had lower chlorophyll levels. At the anatomy level, high Cd concentrations resulted in anatomical abnormalities such as an unusual vascular system, abnormal lignification in the pith parenchyma, and enlarged cortical cells. Moreover, all Cd concentrations resulted in a highly significant decrease in stomatal area and stomatal density (the number of stomata per mm2 leaf area). In addition to growth inhibition, Cd-induced oxidative damage to pea plants as indicated by increased hydrogen peroxide (H2O2) and Malondialdehyde (MDA) levels. To reduce stress toxicity, plants treated with Cd at 50 and 100 (mg/kg) showed a significant increase in antioxidant capacity. Peroxidase (POD) enzyme activity was significantly increased by 41.26 %, 28.64%, 77.05%, and 60.77 % in both seasons, respectively. Si at 300 ppm under Cd (100 mg/kg) stress conductions considerably reduced (MDA) contents by 29.02% and 29.12%, in the two seasons, respectively. The findings pointed out that Si's ability to protect pea against the oxidative stress caused by Cd toxicity.